Die kerk se verantwoordelikheid teenoor die onder-wys: Is Artikel X van die Kerkwet (1986) van die Nederduitsch Hervormde Kerk van Afrika teologies verantwoordbaar? - Botes, H. J. (Hervormde teologiese studies, 1996)
The church's responsibility towards the school: Is Article X of the Church Order (1986) of the Nederduitsch Hervonnde Kerk van Afrika theologically well founded?. This article aims to deal with the selfunderstanding of the Nederduitsch Hervomuie Kerk van Afrika. In particular, attention is given on church polity and its effect on the practical implementation of the church's task to society and specifically towards education. The article also reflects on the role of children in the church, as well as the commitment to the principle of theocracy.